(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The beginning of the XXI century in Russia was marked with large-scale process of public administration reform. It included administrative reform, reform of public service and local self-government.